2010
DOI: 10.4103/0974-8490.62956
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic activity of leaves ofPlectranthus amboinicus(Lour) Spreng in male albino rats

Abstract: The shade-dried powder of leaves of Plectranthus amboinicus (Lour) Spreng was subjected to successive extraction using the various solvents (petroleum ether, chloroform, ethanol and water) in increasing order of polarity. The preliminary phytochemical analyses were carried out for all the extracts. The analyses of the leaves revealed the presence of alkaloids, carbohydrates, glycosides, proteins, amino acids, flavonoids, quinine, tannins, phenolic compounds and terpenoids. Since the phytoconstituents present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…2 In general, are rich source of essential oils, terpenoids and phenol compounds. 3 Pharmacological properties such as anti-inflammatory, 4 antioxidant, 5 antimicrobial, 6 anti-tumoral 7 and diuretic 8 have been demonstrated for several isolated compounds from Plectranthus, corroborating with its larger medicinal uses.…”
Section: Introductionmentioning
confidence: 77%
“…2 In general, are rich source of essential oils, terpenoids and phenol compounds. 3 Pharmacological properties such as anti-inflammatory, 4 antioxidant, 5 antimicrobial, 6 anti-tumoral 7 and diuretic 8 have been demonstrated for several isolated compounds from Plectranthus, corroborating with its larger medicinal uses.…”
Section: Introductionmentioning
confidence: 77%
“…This initiative could encourage the improvement of adherence to pharmacological treatment, offering a product with great popular appeal and pharmacological effects complementary to conventional therapies. [25][26][27][28][29][30][31] In this study, it was shown for the first time that prolonged treatment with an ethanol extract obtained from T. majus is able to prevent the evolution of renovascular hypertension in 2K1C rats, showing a significant reno-and cardioprotective effect. According to previous data, the renin-angiotensin system (RAS) played a prominent role in the oxidative stress and renovascular hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…12 All the rats were kept in good experimental condition and deprived of food for 18 hours before the experiments. 5ml/kg of Normal saline (0.9%) was given orally to the rats before administration of drug or extracts.…”
Section: Evaluation Of Diuretic Activitymentioning
confidence: 99%